2005
DOI: 10.4049/jimmunol.175.3.1593
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Expansion and Differentiation of Vγ9Vδ2 T Cells In Vivo: The Role of Exogenous IL-2

Abstract: Human Vγ9Vδ2 T cells recognize nonpeptidic Ags generated by the 1-deoxy-d-xylulose 5-phosphate (many eubacteria, algae, plants, and Apicomplexa) and mevalonate (eukaryotes, archaebacteria, and certain eubacteria) pathways of isoprenoid synthesis. The potent Vγ9Vδ2 T cell reactivity 1) against certain cancer cells or 2) induced by infectious agents indicates that therapeutic augmentations of Vγ9Vδ2 T cell activities may be clinically beneficial. The functional characteristics of Vγ9Vδ2 T cells from Macaca fasci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 36 publications
5
70
0
Order By: Relevance
“…We have recently demonstrated that HMBPP is associated with antigen-presenting cells and specifically recognized by V␥2V␦2 T cell receptor (TCR) (14). We have also shown that single-dose HMBPP treatment plus IL-2 can induce remarkable expansion of V␥2V␦2 T cells in the blood and prolonged accumulation of V␥2V␦2 T cells in lungs in nonhuman primates (15)(16)(17). V␥2V␦2 T cells accumulating in lungs can re-recognize HMBPP and mount effector function of production of antimicrobial cytokines, IFN-␥, and perforin/granzyme B (17,18).…”
Section: The Possibility That V␥2v␦2 T Effector Cells Can Confer Protmentioning
confidence: 88%
“…We have recently demonstrated that HMBPP is associated with antigen-presenting cells and specifically recognized by V␥2V␦2 T cell receptor (TCR) (14). We have also shown that single-dose HMBPP treatment plus IL-2 can induce remarkable expansion of V␥2V␦2 T cells in the blood and prolonged accumulation of V␥2V␦2 T cells in lungs in nonhuman primates (15)(16)(17). V␥2V␦2 T cells accumulating in lungs can re-recognize HMBPP and mount effector function of production of antimicrobial cytokines, IFN-␥, and perforin/granzyme B (17,18).…”
Section: The Possibility That V␥2v␦2 T Effector Cells Can Confer Protmentioning
confidence: 88%
“…A concern with the prophylactic use of any immunomodulatory compound is the induction of chronic inflammation. Current phosphoantigen-based drugs lead to overt cytokine release in humans (64,65) including the proinflammatory cytokines TNF-␣ and IFN-␥, which would contribute to systemic inflammation in the patient. In a concurrent study, we found that the tannin preparation we tested up-regulated CD11b on ␥␦ T cells, but importantly, did not alter transcript levels for TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…1B, 1C). Furthermore, increasing dose of PAg also augments the rate of proliferating TCRVg9 + gd cells (13,20,21,49) and increasing concentrations of BrHPP rescued the proliferating gd cells from TGF-b inhibition (Fig. 1D, 1E).…”
Section: Resultsmentioning
confidence: 99%
“…TCRVg9 + gd lymphocytes usually represent ∼1% of the circulating mononuclear cells, so their expansion is critically required to bring a significant contribution to cancer immunotherapies. By underlining the negative incidence of TGF-b may have on therapeutic protocols involving in vivo gd cell expansions, this study also provides a rationale for gd cell-based protocols composed of either in vitro expansions (49) or in vivo activation by high-dose PAg supplemented with exogenous IL-2 (12,20,21,25,66,67). In addition, the proliferative response of PAg/IL-2-stimulated gd lymphocytes is essentiallyif not exclusively-mediated by cells from the N and CM compartments of TCRVg9 + lymphocytes (4,8), suggesting that TGF-b might target more selectively these maturation stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation